Mineral Elements, Phenolics and Organic Acids of Leaves and Fruits from Berberis crataegina DC. - Gulsoy, S.; Ozkan, G.; Ozkan, K. (Asian Journal of Chemistry, 2011)
The objective of the study is to determine the elemental composition, phenolic compounds and organic acid concentrations of fruits and leaves from Berberis crataegina DC. Calcium and potassium were the most abundant element in leaves and fruits, respectively. While the calcium concentration of leaves (11130.00 μg/g) was higher than in fruit (2389.00 μg/g), the potassium concentration of fruits (11210.00 μg/g) was the higher than in leaves (7857.00 μg/g). The predominant major phenolic compounds of leaves and fruits were rutin 170.87 mg/kg and chlogenic acid 70.24 mg/kg, respectively. Rutin and apigenin 7-O-glucoside were the highest concentration in fruits. Malic acid and citric acid of leaves were the highest and found as 4338.00 and 155.00 μg/g, respectively. The results showed that the elemental composition, phenolic compounds and organic acid concentrations were obvious difference in fruits and leaves from B. crataegina.